2020
DOI: 10.48550/arxiv.2005.05971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The infinite-dimensional HaPPY code: entanglement wedge reconstruction and dynamics

Abstract: We construct an infinite-dimensional analog of the HaPPY code as a growing series of stabilizer codes defined respective to their Hilbert spaces. The Hilbert spaces are related by isometric maps, which we define explicitly. We construct a Hamiltonian that is compatible with the infinite-dimensional HaPPY code and further study the stabilizer of our code, which has an inherent fractal structure. We use this result to study the dynamics of the code and map a nontrivial bulk Hamiltonian to the boundary. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 17 publications
(30 reference statements)
0
19
1
Order By: Relevance
“…However, entanglement relationships in these models are typically sparse; an averaging procedure is required in order to observe CFT-like behavior. This work stands in contrast to the works [29,32], where nsite correlation functions subsequently were shown to result in either zero or a phase.…”
Section: Conformal Properties Of Hyperinvariant Tensor Networkcontrasting
confidence: 60%
See 1 more Smart Citation
“…However, entanglement relationships in these models are typically sparse; an averaging procedure is required in order to observe CFT-like behavior. This work stands in contrast to the works [29,32], where nsite correlation functions subsequently were shown to result in either zero or a phase.…”
Section: Conformal Properties Of Hyperinvariant Tensor Networkcontrasting
confidence: 60%
“…This behavior is not typically seen in a CFTgroundstate, which generally exhibits long-range quantum en-tanglement. The existence of algebraically decaying correlation functions [32] are a necesary condition for simulation of CFT-groundstates. Jahn et.…”
Section: Introductionmentioning
confidence: 99%
“…To us, this is one of the many examples that show that in order to formulate a complete theory of quantum gravity, one should not work directly at the level of the Hilbert spaces, but rather at the level of the C * -algebra of observables. For example, in order to formulate entanglement wedge reconstruction in a consistent way for systems with operator pushing such as the infinite-dimensional HaPPY code, in contrast to state-pushing in simpler tensor network models [30,31], we have shown that a very similar GNS technique has to be employed [14,15]. Similarly, exact and approximate theorems for entanglement wedge reconstruction work much better by reformulating the problem directly in terms of algebras of observables, as argued in [13].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Another interesting aspect of our approach is that the Gromov boundary lives at infinity, and makes it very natural to define an infinite-dimensional limit of holographic tensor networks. This problem has already been touched upon in [15,16], and more generally, the question of describing holographic quantum error-correction in the language of infinitedimensional operator algebras is an active research program [14,16,17,23]. Here we will see that there is an appropriate way to take the limit of our holographic codes such that they give a net of holographic conditional expectations.…”
Section: Introductionmentioning
confidence: 93%
“…These maps have a few shortcomings, like the fact that they do not create an entangled bulk state. See[15] for another possible choice of Hilbert space maps. However, our maps here have good functorial properties at the level of operators, and will be enough for our purposes.…”
mentioning
confidence: 99%